2020
DOI: 10.3390/en13236405
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mode Adaptive Artificial Neural Network for Dynamic Learning: Application in Renewable Energy Sources Power Generation Prediction

Abstract: A reasonable dataset, which is an essential factor of renewable energy forecasting model development, sometimes is not directly available. Waiting for a substantial amount of training data creates a delay for a model to participate in the electricity market. Also, inappropriate selection of dataset size may lead to inaccurate modeling. Besides, in a multivariate environment, the impact of different variables on the output is often neglected or not adequately addressed. Therefore, in this work, a novel Mode Ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…For a fair comparison we found that only one article is present which also used the same solar dataset. An adaptive artificial neural network is proposed by Zameen and Won [58] and achieved 0.0207 and 0.1438 scores for MSE and RMSE. The results clearly verify and demonstrate that the proposed hybrid approach is suitable and performs better for both energy consumption and generation prediction.…”
Section: Comparative Analysis and Discussionmentioning
confidence: 99%
“…For a fair comparison we found that only one article is present which also used the same solar dataset. An adaptive artificial neural network is proposed by Zameen and Won [58] and achieved 0.0207 and 0.1438 scores for MSE and RMSE. The results clearly verify and demonstrate that the proposed hybrid approach is suitable and performs better for both energy consumption and generation prediction.…”
Section: Comparative Analysis and Discussionmentioning
confidence: 99%
“…Both the solar and wind datasets were considered for the comparative study. The comparison was performed with the most recent method [67], In this section, we compare the proposed method with recent research carried out for power generation forecasting. Both the solar and wind datasets were considered for the comparative study.…”
Section: Assessment With State Of the Artmentioning
confidence: 99%
“…Both the solar and wind datasets were considered for the comparative study. The comparison was performed with the most recent method [67], where a mode-adaptive ANN algorithm is proposed via Spearman's ranking order and population-based algorithms. They evaluate different models such as advanced particle swarm optimization (APSO) and the fine-tuning metaheuristic algorithm (FTMA).…”
Section: Assessment With State Of the Artmentioning
confidence: 99%
“…The output of the proposed ANN controller is the corresponding torque ( C em *) (Gowri and Popuri, 2020). The most appropriate number of hidden layers and their neurons is decided based on an empirical basis in order to attain the required precision of the proposed approach (Donadio et al, 2021; Zamee and Won, 2020). After reiterating the learning algorithms several times.…”
Section: Introductionmentioning
confidence: 99%